THE EFFECTIVENESS OF ANIMATED VIDEOS ON STUDENTS’ WRITING ABILITY IN DESCRIPTIVE TEXT FOR TENTH-GRADE STUDENTS AT SMAN 2 METRO - Shofiatunnisa; Bambang Eko Siagiyanto; Refai (Universitas Muhammadiyah Metro, 2025)
Writing is an essential skill in English language learning, but many students still face challenges in composing descriptive texts due to limited vocabulary, poor grammar, and difficulties in organizing ideas. This research aimed to investigate the effectiveness of animated videos in improving students’ writing ability in descriptive text.This study applied a quantitative method with a quasi-experimental design, involving two classes of tenth-grade students at SMAN 2 Metro in the academic year 2024/2025. Class X.4 was assigned as the experimental class, which was taught using animated videos, while class X.1 served as the control class, taught using conventional methods. The instruments used were writing pretest and post-test, and the data were analyzed using paired sample t-test and independent sample t-test through SPSS 25.The findings showed a significant difference in the students’ writing ability between the experimental and control classes. The Sig. (2-tailed) value was 0.000, which is lower than the significance level of 0.05. It indicates that the use of animated videos had a significant positive effect on students’ ability to write descriptive texts. Therefore, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected.In conclusion, animated videos are effective in enhancing students’ writing performance, especially in developing content, organizing ideas, and improving vocabulary. Animated videos also provide engaging visual support that motivates students in the learning process. Future researchers are encouraged to explore the use of animated videos in other language skills such as listening, speaking, and reading, while considering both benefits and limitations for more optimal learning outcomes.